EPR Effect-Based Tumor Targeted Nanomedicine - Maeda, Hiroshi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
I am honored to undertake the work for Guest Editor for this Special Issue of EPR Effect-Based Tumor Targeted Nanomedicine for the Journal of Personalized Medicine. It has already been 35 years since we published the concept of the EPR effect for the first time. The discovery of the new concept of EPR effect gave an impetus effect of growth momentum in nanomedicine, and numerous works are focused on tumor delivery, although the initial idea was based on vascular permeability in infection-induced inflamed tissue, where we discovered bradykinin in the key mediator of vascular permeability.I know, however, there are pros and cons to EPR effect. Cons stem either from a poor understanding of EPR effect, or somehow a biased view of the EPR effect, or from the tumor models being used, particularly in the clinical settings where vascular blood flow is so frequently obstructed. I hope scientists in the clinic, or basic researchers working on the tumor drug delivery, will join the forum of this Special Issue and express their data and opinions.The scope of this issue includes an in-depth understanding of the EPR effect, and issues associated with tumor microenvironment and also further exploitation of EPR effect in human cancer. In addition, new strategies for enhancement of the EPR effect using nanomedicine will be welcome, which is as important as the EPR effect itself. These papers cover not only cancer therapy, but also imaging techniques using nanofluorescent agents, including photodynamic therapy for inflammation, and boron neutron capture therapy.